2014
DOI: 10.1016/j.jval.2014.08.1556
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Surgical Management of Stress Urinary Incontinence With Single-Incision Mini-Sling Versus Tension-Free Vaginal Obturator in Spain

Abstract: A509 loss by 94, 76 and 87% respectively. The cost per case avoided would be 165 Euros, and cost per hospitalization avoided would be 1,639 Euros with implementation of universal vaccination. The cost per QALY saved would be 29,452 Euros and 20,453 Euros from the health care and societal perspectives respectively. ConClusions: RV5 is projected to avert substantial number of RGE hospitalizations and office visits in Slovenia and would be considered a cost effective intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Seven studies were based in the US [14][15][16][17][18][19][20], six in the UK [21][22][23][24][25][26], six in Canada [27][28][29][30][31][32], two in Spain [33,34], one in Australia [35], one in Bosnia and Herzegovina [36], one in Finland [37], one in Italy [38] and one in the Netherlands [39]. Thirteen studies were model-based analyses [14][15][16][17][18][19][20][21][22][23][27][28][29], seven studies were within-trial evaluations [24-26, 30, 31, 37, 38], five were retrospective data analyses [32,33,35,36,40] and one was prospective non-randomised study [34]. Of the model-based studies, eight studies used a Markov model [14,…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies were based in the US [14][15][16][17][18][19][20], six in the UK [21][22][23][24][25][26], six in Canada [27][28][29][30][31][32], two in Spain [33,34], one in Australia [35], one in Bosnia and Herzegovina [36], one in Finland [37], one in Italy [38] and one in the Netherlands [39]. Thirteen studies were model-based analyses [14][15][16][17][18][19][20][21][22][23][27][28][29], seven studies were within-trial evaluations [24-26, 30, 31, 37, 38], five were retrospective data analyses [32,33,35,36,40] and one was prospective non-randomised study [34]. Of the model-based studies, eight studies used a Markov model [14,…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%
“…Of the model-based studies, eight studies used a Markov model [14,15,17,19,[21][22][23]27] and five used a decision tree [16,18,20,28,29]. Sixteen studies were CUA [14-17, 19-26, 30, 31, 34, 38], four were CEA [28,29,32,37], four were CCA [18,27,35,40], one was a CMA [33] and one was a CBA [36]. Fifteen studies reported a health service perspective [17, 19-22, 24-29, 32-34, 38], two studies reported a societal perspective [14,37], one study reported a third-party payer perspective [16], two studies reported a public payer perspective [30,31] and six studies did not report a perspective [15,18,23,35,36,40].…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations